Fundamentals of regression modeling - Babones, Salvatore J. (Sage benchmarks in social research methods., 2013)
This new four-volume major work presents a collection of landmark studies on the topic of regression modeling, identifying the most important, fundamental articles out of thousands of relevant contributions.